COMMUNITY PERSPECTIVES ON THE EXISTENCE OF WILDLIFE (CASE STUDY IN TALANG PONIJAN AND SIDODADI I) - Elsa Nadia Almaidah; Indra Gumay Febryano; Dian Iswandaru; Hari Kaskoyo; Christine Wulandari; Arief Darmawan; Yulia Rahma Fitriana; Novriyanti; Susni Herwanti; Rahmat Safe'i (Jurnal Belantara, 2025)
Community perspectives are important for wildlife, as they impact their contribution to wildlife conservation. This study aims to analyze community perspectives on wildlife in the Talang Ponijan and Sidodadi I forest farmer groups, Lampung Province, Indonesia. The method in this study uses a qualitative approach through in-depth interviews, involved observation, and documentation studies. The data collected was analyzed descriptively to illustrate how the community's perspective on the existence of wildlife. The results showed that there are similarities in the views of the Talang Ponijan and Sidodadi I communities towards the existence of wildlife. The people of Talang Ponijan and Sidodadi I have a negative view of the existence of wild boar (Sus scrofa), bear (Helarctos malayanus), bajing (Callosciurus notatus), tiger (Panthera tigris), monkey (Macaca fascicularis), and macaque (Macaca nemestrina). Negative views arise because they are considered crop pests and destroy gardens. They are also considered a nuisance and a threat to safety. Gibbon (Symphalangus syndactylus), bats (Chiroptera sp.), and birds have a positive impact as they act as seed dispersers, pest controllers, and coffee quality indicators. However, their behavior towards wildlife sustainability shows differences. Some people in Talang Ponijan are still involved in practices that harm wildlife, such as monoculture, poaching and land clearing. Meanwhile, the Sidodadi I community tends to prioritize wildlife-sustainable agricultural practices such as shade coffee systems and planting high canopy trees. The government needs to provide guidance to increase community capacity and strict and effective law enforcement is important to prevent illegal activities.